A Study of Investment Awareness and Patterns of Savings and Investments by Rural Investors - Lokhande, Murlidhar A. (Indian Journal of Finance, 2015)
The nature of financial markets has changed drastically. Investing money has become a very complex task because of the huge number of savings and investment companies and products offered by them, terms and conditions of investments, and prevalent complex rules and regulations. Most of the investors, particularly rural investors, are found to be unaware about investment avenues and rules and regulations. In spite of remarkable growth of our economy and increasing income levels of people, the pace of savings mobilization is lower in India. Rural savings are not mobilized and invested properly. Investment is an economic activity which creates capital required for various sectors of the economy. So, every earning person should be motivated to save and invest his/her money. The study attempted to find out the awareness levels of rural investors about various investment avenues, their preferences, and considerations for investing money. A sample of 300 respondents was selected from four villages from Sillod block of Aurangabad district, Maharashtra. The major focus of the study was on investigating whether there was a difference between investment awareness levels and educational qualifications of male and female rural investors. The study disclosed that there was no significant difference in awareness levels of rural male and female investors and their educational qualifications. The investment preference order of the respondents indicated that they wished to park their investments in 'safe' options only. Bank deposits, gold and jewelry, real estate were popular investment avenues for a majority of the investors.